Radiographic evaluation of the normal ankle joint in children and adolescent - Sung, Ki Hyuk; Kwon, Soon Sun; Moon, Seung Jun; Lee, Seung Yeol (Journal of Orthopaedic Science, 2018)
Background: The purpose of this study was to determine the reliability of numerous radiographic measurements of the skeletally immature ankle joint, timing of ossification of medial malleolus and appearance of tibial incisura and differences in the values of radiographic measurements based on age and sex. Methods: This study included 590 subjects (0–15 years), who underwent ankle AP, lateral and mortise radiographs. Presence of the medial malleolus and incisura fibularis were recorded. Tibiofibular overlap, tibiofibular clear space, medial clear space, talar tilt, talocrural angle, relative fibular width and fibular position were measured. Results: All radiographic measurements showed good to excellent intraobserver and interobserver reliability (ICCs, 0.603 to 0.949). The timing of ossification of medial malleolus and appearance of tibial incisura between boys and girls were not different. Tibiofibular clear space on mortise views, and medial clear space on AP and mortise view significantly decreased by age. Tibiofibular overlap on AP and mortise views, relative fibular width on AP view significantly increased by age. Talocrural angle, tibiofibular overlap on AP view, tibiofibular clear space on AP and mortise views, medial clear space on AP and mortise views and fibular position were significantly larger in boys than in girls. The difference in tibiofibular overlap, tibiofibular clear space and medial clear space on AP view of both sides was <50% in 97.1%, 93.1%, and 97.2% of patients, respectively. The difference in tibiofibular overlap, tibiofibular clear space and medial clear space on mortise view of both sides was <50% in 98.0%, 96.5%, and 100% of patients, respectively. Conclusions: For skeletally immature patients, the criteria for absolute radiographic values used in adults to assess distal tibiofibular syndesmosis or deltoid ligament injury cannot be applied, but comparison of both sides of ankle joint could help physicians to predict the need for additional evaluations.
Keywords: Adolescent; Age Factors; Ankle Joint; Child; Child, Preschool; Cohort Studies; Female; Humans; Male; Observer Variation; Radiography; Reference Values; Republic of Korea; Retrospective Studies; Sex Factors